Biochar reduces nutrient loss and improves microbial biomass of composted cattle manure and maize straw. (19th February 2020) - Bello, Ayodeji; Deng, Liting; Sheng, Siyuan; Jiang, Xin; Yang, Wei; Meng, Qingxin; Wu, Xiaotong; Han, Yue; Zhu, Haifeng; Xu, Xiuhong
Abstract: In this study, nutrient loss, the direct and indirect relationship between period, compost types, temperature, total nitrogen (TN), nitrate nitrogen (NO3 − ‐N), ammonium nitrogen (NH4 + ‐N), microbial biomass carbon (MBC), and microbial biomass nitrogen (MBN) were investigated during composting of cattle manure–maize straw mixture. This study findings revealed that biochar addition lowered NH4 + ‐N but did not increase NO3 − ‐N concentrations unlike no biochar piles during composting. The first‐order kinetic models showed that biochar accelerated organic matter (OM) degradation and improved nitrogen mineralization, consequently reducing TN losses by 13.6% and OM losses by 12.66%. Transformation ratio of MBC/MBN, coupled with other chemical components of the entire microbial community, suggested a shift in the microbial succession and diversity during composting from the dominant bacteria and actinomycetes to fungi. The structural equation model and path coefficient revealed temperature to be the main factor mediating the evolution of MBC and MBN in composting. The physicochemical variables, phytotoxicity, and final product quality revealed that biochar incorporation to the composting feedstock is an ideal material for mitigating problems of TN and OM losses in composting and ultimately enhancing the fertility potential of the final compost product. Abstract : Evolution of microbial biomasses; Variation of organic matter and total carbon; Dynamics of nutrient losses and Structural equation models (SEM).